Are institutional nominee directors required? - Patil, R.H. (2001)
Given the context of promoter family control of management of companies in India and the relatively poor quality of corporate governance, institutional shareholders would be doing a great disservice to themselves and to the diffused class of small shareholders if they shirk their responsibility of taking interest in the quality of management of the companies in which they have a large shareholding. - Reproduced
Keywords: Financial markets